Estimation of the propulsive force by arm stroke in the front crawl swimming - Suito, H.; Takahashi, S.; Tsujimoto, N.; Shinkai, H.; Sano, S.; Nunome, H.; Ikegami, Y. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
The purpose of this study was to investigate the propulsive forces from fluid forces acting on the hand in the 100 m front crawl swimming. Subjects in this study were 14 males Japanese competitive swimmers (Age = 20.1 ± 1.2 years, Height = 173.4 ± 6.2 cm, Weight = 67.7 ± 6.4 kg, 100 m season best time = 56.74 ± 3.73 s). The right arm stroke motions of the subjects were captured three-dimensionally cinematographic procedures at 60 Hz in the positions of 15 m and 65 m from the start. Each trial was digitized from the entry of the right hand to the water to the release of the right hand from the water. The fluid forces acting on the hand was estimated using the drag and lift coefficients by Schleihauf (1979). The average swimming velocity was 1.66 ± 0.12 (m/s). The average hand velocity was 2.43 ± 0.15 (m/s). Estimated peaks of the fluid forces acting on the hand in the front crawl swimming were observed pull phase and push phase. Estimated peaks of the propulsive force acting on the hand also were observed pull phase and push phase. Moreover, the ratio of the drag and lift that composes the propulsive force was calculated. The ratio of the drag and lift that composes the propulsive force was 56.6 ± 9.5 % and 43.4 ± 9.5 %, respectively. The drag force in propulsive force was larger in pull phase than push phase. On the other hand, the lift force in propulsive force was larger in push phase than pull phase. There was a significant the average swimming velocity with the ratio of drag and lift to propulsive force (r = -0.703, P < 0.01). Thus, in the propulsive force of the high performance swimmer, drag force was dominant. However, there were not a significant correlation between the average swimming velocity and the average impulse of the propulsive force. In conclusion, this study would like to state the following two points. First, the propulsive force on the hand in the front crawl swimming was dominant drag force in pull phase and dominant lift force in push phase. Second, the higher performance swimmers were larger the ratio of the drag force in propulsive force.